3(2b+4)=4b-2(5-b)

Simple and best practice solution for 3(2b+4)=4b-2(5-b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2b+4)=4b-2(5-b) equation:



3(2b+4)=4b-2(5-b)
We move all terms to the left:
3(2b+4)-(4b-2(5-b))=0
We add all the numbers together, and all the variables
3(2b+4)-(4b-2(-1b+5))=0
We multiply parentheses
6b-(4b-2(-1b+5))+12=0
We calculate terms in parentheses: -(4b-2(-1b+5)), so:
4b-2(-1b+5)
We multiply parentheses
4b+2b-10
We add all the numbers together, and all the variables
6b-10
Back to the equation:
-(6b-10)
We get rid of parentheses
6b-6b+10+12=0
We add all the numbers together, and all the variables
22!=0
There is no solution for this equation

See similar equations:

| -5+-2g=-3 | | 3t-2=2(t+4) | | 18a=40 | | 2x-5x+11=34 | | (z+3÷5)-1/4=3/4 | | 8(z+3)= 32 | | 8(z+3)=  32 | | 7x+8=28+2x | | -5/8+n=5/6 | | 3y=2=-19 | | 2/3w=240 | | -5/6=-1/3x | | 4y+6/y-3=2 | | t-3/8=-5/6 | | z+94=4 | | 1/3+s=2/5 | | 0.q-0.2(3q+4)=-0.3(5q+) | | -(6m+8=4(17m | | 9(b+7)=729 | | 10x-6=23+5 | | (5x+1)(x−3)=0 | | 8w+2=3w+12 | | -2(24+6z)=-65 | | 45-4x=89 | | (X-4)3=(2x+1) | | 4x+x5=21 | | 8w=6w+8 | | s/20=3.8 | | 1008=2x^2 | | k-4.97=4.13 | | x+40+3x=52x=4 | | w/3=3.49 |

Equations solver categories